The Borrowers. - Norton, Mary.; Krush, Beth - illus; Krush, Joe - illus (New York : Harcourt, Brace, 1953)
Miniature people who live in an old country house by borrowing things from the humans are forced to emigrate from their home under the clock.
Keywords: Fantasy